Effect of carbonate content on the in vitro bioactivity of carbonated hydroxyapatite. Issue 13 (1st July 2022) - Safarzadeh, Marjan; Chee, Chin Fei; Ramesh, S.
Abstract: The effect of carbonate content on the apatite-forming ability of carbonated hydroxyapatite (CHA) in simulated body fluid (SBF) has been investigated. Five different nanocrystalline B-type CHA with carbonate content ranged from 2.01 to 5.25 wt% were prepared, sintered, and assessed for their in vitro bioactivity in SBF solution for 7-weeks under static conditions at 36.5 °C. The formation of the apatite layer and the surface morphology of CHA were examined by using a scanning electron microscope (FESEM) at week 1, 3, and 7 of SBF immersion, respectively. The Ca/P molar ratio of the CHA was determined by X-ray fluorescence (XRF). In addition, the sample weight changes and the pH of the SBF solution were measured. The results show that the formation of apatite layer depends on the carbonate content of CHA. Increasing the carbonate content caused significant increases in the surface area of CHA and the rate of apatite formation. Weight loss was observed for all CHA samples during the first week of SBF immersion, and thereafter followed by weight regain weekly until week 7. The changes in the pH of SBF and the Ca/P molar ratio were proportional to the carbonate content of CHA. This study thus highlights the importance of determining carbonate content aspect that govern the bioactivity of CHA.